(untitled) (Comprehensive Journal of Science, 2025)
This study presents a comprehensive systematic review comparing the effectiveness of e-learning and traditional education, focusing on students’ academic achievement across different educational levels (primary, secondary, and higher education) between 2001 and 2024. The importance of this research lies in its response to accelerated digital transformations, especially after the COVID-19 pandemic, providing evidence-based insights for educational policymakers and instructional designers. The objectives are to examine the impact of learning modes (online, traditional, blended) on academic performance and to identify contextual factors such as discipline, instructional design, and socio-economic conditions. The methodology followed a systematic review framework using PICOS criteria, analyzing 13 empirical and meta-analytic studies. Data quality was assessed using Cochrane RoB and AMSTAR-2. Results show that e-learning produced comparable or superior outcomes in some contexts, while traditional learning outperformed in practical, lab-based disciplines. Blended learning emerged as the most effective approach overall. Recent studies highlighted the potential of immersive technologies such as the Metaverse and interactive discussion platforms in enhancing engagement and achievement. The study recommends conducting longitudinal research, standardizing academic achievement measures, and further exploring immersive learning environments.